The efficacy and safety of a new reduced-toxicity conditioning with 4 days of once-daily 100 mg/m2 intravenous busulfan associated with fludarabine and antithymocyte globulins prior to allogeneic stem cell transplantation in patients with high-risk myelodysplastic syndrome or acute leukemia. Issue 10 (2nd October 2016) - Wanquet, Anne; Crocchiolo, Roberto; Furst, Sabine; Granata, Angela; Faucher, Catherine; Devillier, Raynier; Harbi, Samia; Lemarie, Claude; Calmels, Boris; Vey, Norbert; Weiller, Pierre Jean; Chabannon, Christian; et al.
Abstract: The optimal intensity of myeloablation associated with a reduced-toxicity conditioning (RTC) regimen in order to decrease the relapse rate without increasing non-relapse mortality (NRM), is not well established yet. This retrospective analysis was done on 30 patients with hematological malignancies. The aim was to assess the safety of a RTC regimen based on the busulfan at a dose of 100 mg/m 2 /d intravenously for 4 d, fludarabine at a dose of 30 mg/m 2 /d for 5 d, and anti-thymoglobulins at a dose of 2.5 mg/kg/d for 2 d. The cumulative incidences of grade 2–4 acute graft-versus-host disease (GVHD) and all grades chronic GVHD were 37% and 42%, respectively. Median 1-year overall survival and disease-free survival were 66% and 50%, respectively. At 1 year, the cumulative incidence of relapse/disease progression was 33%. NRM was 3% and 17% at day 100 and 1 year, respectively. This RTC conditioning regimen can lead to a long-term disease control. Moreover, it appears to be safe with a low NRM rate among high-risk patients.